UJI AKURASI INSTRUMEN UNI-ONE TRACKER DALAM PENENTUAN RUKYATUL HILAL - Farid, Firdaus; Fatmawati; Akib, Faisal (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses the Uni-One Tracker instrument which was developed by a team of students from the Astronomy Study Program at UIN Alauddin Makassar and is used in the implementation of the Rukyatul Hilal to determine the beginning of the lunar month. The purpose of this study was to determine the components and methods of using the Uni-One Tracker instrument and the level of accuracy in determining the hilal rukyatul. The method used is field research with a qualitative descriptive approach and collecting primary and secondary data. The results showed that the components of the Uni-One Tracker instrument consisted of location gates, dial boards, mobile phone holders, tripods, waterpass, and dipotra applications. The method of use includes several steps, namely installing, leveling, aiming at the horizon, setting the dioptra application, aiming at the sun, and observing the new moon. The observation results show that the Uni-One Tracker instrument is accurate in localizing the new moon's position at the beginning of the lunar month, with the difference in azimuth and the difference in the height of the new moon not more than one degree compared to the theodolite as a comparison tool. An important finding from this study is that the Uni-One Tracker instrument can be a simple and accurate tool option in the implementation of the Hilal Rukyatul. This research can be a reference for the development of methods for carrying out the Rukyatul Hilal in the future.